2004
DOI: 10.1016/j.jacc.2003.10.055
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biphasic waveform design on post-resuscitation myocardial function

Abstract: Maximum survival and minimum myocardial dysfunction were observed with the low-capacitance 150-J waveform, which delivered higher peak current while minimizing energy and average current.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…This injury is more evident when defibrillation is administered in the second and third phases of cardiac arrest that the heart is exposed to severe ischemic or acidic conditions [64]. The electrical shocks increase intramyocardial temperature leading to myocardial damage [65], potentiate excitationcontraction uncoupling, and are linked with dose-dependent release of free radicals and waveform-specific effects on mitochondrial function [66]. Biphasic waveforms are associated with less injurious effects on myocardial oxidative metabolism and hemodynamic performance [66].…”
Section: Pathophysiological Disturbances and Hemodynamics During Cardmentioning
confidence: 99%
“…This injury is more evident when defibrillation is administered in the second and third phases of cardiac arrest that the heart is exposed to severe ischemic or acidic conditions [64]. The electrical shocks increase intramyocardial temperature leading to myocardial damage [65], potentiate excitationcontraction uncoupling, and are linked with dose-dependent release of free radicals and waveform-specific effects on mitochondrial function [66]. Biphasic waveforms are associated with less injurious effects on myocardial oxidative metabolism and hemodynamic performance [66].…”
Section: Pathophysiological Disturbances and Hemodynamics During Cardmentioning
confidence: 99%
“…33 We observed that biphasic compared with monophasic waveform defibrillation shortened the time from first shock to sustained ROSC by nearly 3 minutes. That this difference was not statistically significant could be because the study was underpowered or because a waveform effect, if present, was attenuated by the severity of cardiac dysfunction that accompanies protracted VF.…”
Section: Shock Energymentioning
confidence: 71%
“…New approaches are being developed to optimize the effectiveness of electrical defibrillation by identifying the proper timing for shock delivery and by using safer and more effective defibrillation waveforms. (24,25) …”
Section: Decreased Left Ventricular Compliancementioning
confidence: 99%